2021
DOI: 10.1007/s40120-021-00261-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Infection, Vaccination, and Guillain–Barré Syndrome: A Review

Abstract: Guillain–Barré syndrome (GBS) is an autoimmune disorder of the peripheral nervous system that typically develops within 4 weeks after infection. In addition to conventional infectious diseases with which we are familiar, emerging infectious diseases, such as Zika virus infection and coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), have also been suggested to be associated with GBS. GBS is mainly categorized into a demyelinating subtype known as acute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
54
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 90 publications
1
54
0
Order By: Relevance
“…Similar to previous reviews on GBS associated with COVID-19, we found that both COVID-19 and COVID-19 vaccination mostly cause the classic form of GBS (under the clinical diagnosis classification) and the acute inflammatory demyelinating polyneuropathy subtype (based on electrodiagnostic features) within 2 weeks of infection or vaccination ( 6 8 ). However, the bilateral facial palsy with paresthesia variant and initial onset symptoms of facial diplegia were more frequently found in GBS case-patients after COVID-19 vaccination.…”
supporting
confidence: 88%
“…Similar to previous reviews on GBS associated with COVID-19, we found that both COVID-19 and COVID-19 vaccination mostly cause the classic form of GBS (under the clinical diagnosis classification) and the acute inflammatory demyelinating polyneuropathy subtype (based on electrodiagnostic features) within 2 weeks of infection or vaccination ( 6 8 ). However, the bilateral facial palsy with paresthesia variant and initial onset symptoms of facial diplegia were more frequently found in GBS case-patients after COVID-19 vaccination.…”
supporting
confidence: 88%
“…With this respect, we can speculate that a late autoimmunity reaction might have occurred with a molecular mimicry mechanism [5], probably after seroconversion. Accordingly, in our patient, SARS-CoV-2 IgG antibodies were detected in the serum, feasibly responsible of the onset of the molecular mimicry process [5], although antiganglioside antibodies were not found. However, this hypothesis cannot be confirmed due to the nature of this case report.…”
mentioning
confidence: 95%
“…Despite the controversial link between this neurologic pathology and SARS-CoV-2 vaccination [5], the risk-benefit ratio clearly recommends the vaccination due to its efficacy in reducing the morbidity and mortality for COVID-19 [1]. The first report on the possible association between GBS and vaccination was in 1976 during the mass vaccination campaign against Swine Influenza in the USA, with an eightfold rise in the incidence of GBS in those vaccinated (4.9-5.9/1,000,000) [5]. However, further studies trying to assess this relation in other type of vaccines revealed inconsistent results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GBS has also been extensively reported after Covid-19 infection: AIDP is the most common form, but acute motor axonal neuropathy and AMSAN variants have also been described; the suspected pathogenetic mechanism is para-infectious, anti-ganglioside antibodies (including anti-GM1, GM2, GD1a and GQ1b) have been detected and clinical features include a more severe weakness and more frequent need of intensive care unit admission when compared to GBS not related to Covid-19 [ 7 ].…”
mentioning
confidence: 99%